IMPLEMENTASI PERATURAN DAERAH KOTA SEMARANG NOMOR 7 TAHUN 2010 TENTANG PENATAAN RUANG TERBUKA HIJAU AREA TAMAN DI KECAMATAN TEMBALANG - Ninik Setiyaningrum; Aloysius Rengga (Journal of Public Policy and Management Review, 2016)
Tembalang region is one of expansion are in Semarang City that used for regional center of educationl development and housing and settlements. Tembalang as education center have an impact on the increasing number of settlement. Along with the development of the region Tembalang existence og green space park increasing pressured by growing over the land that ist not awakened into smaller plots. Therefore, the government of Semarang creat a Regional Regulation of Semarang City Number 7 years 2010 on spactial planning open green space. The method used in this research is the metod deskriptif kualitatif with document collection surveys, interviews and documentation. Reasearch results show that implementation of policy arrangement of green open space parkland yet walking in accordance with regional regulatioan of semarang city number 7 years 2010. The factor that encourage and impede the implementation of policies is the spatial redources, communications, disposition and bureaucratic structure. The main factor that impedes is a resource in the form of resource and budget financial. There are some suggestions that can be done to overcome barriers such as adding the amoint of budget in accprdance with needs required in Semarang City budget. An increase in the quantity and quality of human resources. Improved the quality of human resources with education and training and to improve coordination with the public to support the policy about green pen space.